2022
DOI: 10.1103/physrevapplied.17.024028
|View full text |Cite
|
Sign up to set email alerts
|

Exponential Escape Rate of Filamentary Incubation in Mott Spiking Neurons

Abstract: Mott materials such as vanadium oxides, when subject to a strong applied voltage, present an inhomogeneous insulator-to-metal transition with formation of metallic filaments within the insulating bulk. This property is enabling the development of compact and power-efficient neuromorphic devices known as Mott neurons. However, the nature of the transition has not been fully understood yet, as it may be attributed to different effects, including Joule self-heating and hot-carrier injection. Moreover, the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
(83 reference statements)
0
19
0
Order By: Relevance
“…It should be kept in mind that the interaction should be a priori scalable to multiple neurons, since building networks is the ultimate goal. Since Mott neurons rely on an electro-thermal incubation process 157 we envision different types of neuron-neuron interactions based on both electric and thermal coupling.…”
Section: Neural Network a Charge Currentsmentioning
confidence: 99%
“…It should be kept in mind that the interaction should be a priori scalable to multiple neurons, since building networks is the ultimate goal. Since Mott neurons rely on an electro-thermal incubation process 157 we envision different types of neuron-neuron interactions based on both electric and thermal coupling.…”
Section: Neural Network a Charge Currentsmentioning
confidence: 99%
“…After releasing the voltage the device relaxes back to the original high resistance state (HRS). These volatile resistive switches exhibit excellent characteristics with stable and reproducible operation up to 10 9 cycles, and simple circuits including one or two VO 2 switches, capacitors, resistors, and batteries can realize artificial neurons that can mimic most of the known biological neuronal dynamic patterns. ,,,, Alternatively, the underlying switching mechanism exhibits remarkable complexity both in the temporal and spatial domains. The former is reflected in the subthreshold switching characteristics for rapidly repeated programming pulses, whereas spatially an inhomogeneous switching region was discovered, where the formation of conductive regions is more pronounced at the device edges. , The description of these phenomena requires complex modeling tools, like a percolation network model. …”
Section: Introductionmentioning
confidence: 99%
“…Besides the structural and electronic properties, the optical features also change remarkably between the two phases. Due to the near room temperature phase transition, VO 2 is an attractive material for various applications including electromechanical devices, sensors and transistors. Recently, the advantageous properties of VO 2 were also exploited in the field of neuromorphic computing, taking advantage of the volatile resistive switching characteristics of VO 2 devices. …”
Section: Introductionmentioning
confidence: 99%
“…
important research topic because most of the critical properties of Mott neuromorphic devices, such as the firing rate of artificial neurons [3][4][5][6][7] and the potentiation/ depression rate and temporal plasticity of artificial synapses, [5,8] directly depend on the formation/retention time of the metallic phases, as well as because of the fundamental interest in the physics of the transition pathway. [9][10][11][12][13] In previous studies, dynamics analysis and performance characterization of the metal-insulator transition have been conducted by fabricating two-terminal electrodes on a material and inducing the transition via electric field application or current injection.
…”
mentioning
confidence: 99%
“…[9][10][11][12][13] In previous studies, dynamics analysis and performance characterization of the metal-insulator transition have been conducted by fabricating two-terminal electrodes on a material and inducing the transition via electric field application or current injection. Using the resistance changes under fields as a probe of the formation of the metallic phase, the dynamics and speed of the transition have been investigated for a variety of strongly correlated materials, including vanadium oxides (VO 2 , V 2 O 3 , and V 3 O 5 ), [5][6][7][9][10][11][13][14][15] metal chalcogenides (AM 4 X 8 (A = Ga and Ge, M = V, Nb, and Ta, X = S and Se), [3,4,8,[16][17][18][19] Ni(S,Se) 2 , [19] and 1T-TaS 2 [20,21] ), and rare-earth perovskite manganites [22] and nickelates, [12] and high-speed resistive switching with a switching time down to <100 ns has been demonstrated in some materials. [6,11,12,17,20] Recent investigations have indicated that the electrically driven resistive switching in the strongly correlated materials is generally produced by the increase in the internal temperature due to Joule heating, and temperature-driven metal-insulator transitions that are the same as those induced by temperature In Mott-type resistive switching phenomena, which are based on the metalinsulator transition in strongly correlated materials, the presence of an abrupt temperature-driven transition in the material is considered essential for achieving high-speed and large-resistance-ratio switching.…”
mentioning
confidence: 99%